2022
DOI: 10.1021/acsami.2c14754
|View full text |Cite
|
Sign up to set email alerts
|

Improved Recovery of Captured Airborne Bacteria and Viruses with Liquid-Coated Air Filters

Abstract: The COVID-19 pandemic has revealed the importance of the detection of airborne pathogens. Here, we present composite air filters featuring a bioinspired liquid coating that facilitates the removal of captured aerosolized bacteria and viruses for further analysis. We tested three types of air filters: commercial polytetrafluoroethylene (PTFE), which is well known for creating stable liquid coatings, commercial high-efficiency particulate air (HEPA) filters, which are widely used, and in-house-manufactured cellu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 68 publications
0
5
0
Order By: Relevance
“…In addition, findings of long-distance aerial dispersal have been reported ( 43 , 44 ), which further affirms the utility of this device for long-range detection. Furthermore, the device we employed utilized liquid-coated collection substrates, which can improve the retrieval rate of airborne pathogens such as SARS-CoV-2 ( 45 ). Notably, we were able to detect viral RNA through N95 respirators and surgical masks in the C+ facility (Hot and Warm areas).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, findings of long-distance aerial dispersal have been reported ( 43 , 44 ), which further affirms the utility of this device for long-range detection. Furthermore, the device we employed utilized liquid-coated collection substrates, which can improve the retrieval rate of airborne pathogens such as SARS-CoV-2 ( 45 ). Notably, we were able to detect viral RNA through N95 respirators and surgical masks in the C+ facility (Hot and Warm areas).…”
Section: Discussionmentioning
confidence: 99%
“…When airborne, they can be easily spread but difficult to detect. 105 In 2021, Regan and colleagues 106 reported on a liquid-infused HEPA membrane system designed to capture and sequester viruses from viruscontaining aerosols filtered from large volumes of air. They hypothesized that the presence of the liquid coating would make it easier to recover and analyze the viruses in the aerosols to provide more information on the types and, importantly, the infectiousness of these pathogens.…”
Section: Secondary Component: Virus-containing Aerosolsmentioning
confidence: 99%
“…In addition, several agencies have predicted a continued risk of both the emergence and re-emergence of viral diseases . Thus, it is critical to develop preemptive quarantine strategies for the rapid and easy diagnosis of potentially infected people to prevent and control future epidemics. , Recent studies have reported the development of various technologies to capture, measure, and detect bioaerosol-mediated infections. Specifically, biosensors for bioaerosol detection are being developed using various technologies to increase detection sensitivity, shorten analysis time, and ease of use including gold nanoparticles modified carbon electrode-based sensors, DNA-antibody complex-base electrochemical sensors, and gold nanoparticles-based lateral flow immunoassay (LFIA) …”
Section: Introductionmentioning
confidence: 99%